A multiple peak adaptive landscape based on feeding strategies and roosting ecology shaped the evolution of cranial covariance structure and morphological differentiation in phyllostomid bats. (26th March 2019) - Rossoni, Daniela M.; Costa, Bárbara M. A.; Giannini, Norberto P.; Marroig, Gabriel
Abstract: We explored the evolution of morphological integration in the most noteworthy example of adaptive radiation in mammals, the New World leaf‐nosed bats, using a massive dataset and by combining phylogenetic comparative methods and quantitative genetic approaches. We demonstrated that the phenotypic covariance structure remained conserved on a broader phylogenetic scale but also showed a substantial divergence between interclade comparisons. Most of the phylogenetic structure in the integration space can be explained by splits at the beginning of the diversification of major clades. Our results provide evidence for a multiple peak adaptive landscape in the evolution of cranial covariance structure and morphological differentiation, based upon diet and roosting ecology. In this scenario, the successful radiation of phyllostomid bats was triggered by the diversification of dietary and roosting strategies, and the invasion of these new adaptive zones lead to changes in phenotypic covariance structure and average morphology. Our results suggest that intense natural selection preceded the invasion of these new adaptive zones and played a fundamental role in shaping cranial covariance structure and morphological differentiation in this hyperdiverse clade of mammals. Finally, our study demonstrates the power of combining comparative methods and quantitative genetic approaches when investigating the evolution of complex morphologies.